ANALISIS PENGARUH KOMUNIKASI DAN DIKLAT TERHADAP KINERJA PEGAWAI DINAS PARIWISATA DAN SENI BUDAYA KOTA - herlan junaidi; mokhamad said (JURNAL KOMPETITIF, 2015)
“The impact of Communication and Training on public servant’s perfomance at Dinas Pariwisata Dan Seni Budaya Kota Pagar Alam”. Data from sample of 54 public servant from Dinas Pariwisata Dan Seni Budaya Kota Pagar Alam were analysed using multi – regression modelling technique. The result indicate that the direct impact of Communication and Training on public servant’s performance are positive and significant as hypothesized. Furthermore, Communication and Training partially influences the performance. Chief officer can implement Communication and Training, therefore expect improved the public servant’s performance of Dinas Pariwisata Dan Seni Budaya Kota Pagar Alam. Keywords: Communication, Training, Public Servant’s Performance, Multi Regression Modelling Technique.